2011
DOI: 10.1007/s00247-011-2108-1
|View full text |Cite
|
Sign up to set email alerts
|

Oncological imaging: tumor surveillance in children

Abstract: As the need for accurate diagnostic imaging often continues throughout a cancer survivor’s life, imaging methods with the least toxicity must be used so as to provide needed information without contributing to long-term sequelae that might compound toxicities inherent with the primary disease and its treatment. In this regard, the costs, benefits and potential risks of post-therapy monitoring for disease recurrence warrant periodic review. Unfortunately, few analyses are available regarding the impact of surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…We also found that in addition to history/symptoms and UCats, MIBG scans detected the majority of recurrences. However, our study and several other reports of surveillance imaging for non‐NB pediatric cancers have not shown that early detection is associated with improved salvage rates or survival . Further support to decrease the use of CT specifically for pulmonary metastatic disease at recurrence was recently demonstrated in another single institution study.…”
Section: Discussionmentioning
confidence: 38%
See 1 more Smart Citation
“…We also found that in addition to history/symptoms and UCats, MIBG scans detected the majority of recurrences. However, our study and several other reports of surveillance imaging for non‐NB pediatric cancers have not shown that early detection is associated with improved salvage rates or survival . Further support to decrease the use of CT specifically for pulmonary metastatic disease at recurrence was recently demonstrated in another single institution study.…”
Section: Discussionmentioning
confidence: 38%
“…It is also more user‐dependent, with greater variability in experience between imaging centers. Finally, for the majority of pediatric cancers, including NB, there is no evidence that early detection of recurrence on surveillance imaging is associated with improved salvage rates or impacts overall survival …”
Section: Introductionmentioning
confidence: 99%
“…Because approximately 90% of children with Wilms tumor can be cured with contemporary therapy13 and a significant proportion of those who relapse can be salvaged,12‐14 the utility of routine, off‐therapy surveillance imaging is controversial 3‐6, 23. It is also unclear whether the use of imaging to detect clinically asymptomatic disease recurrence in the abdomen and pelvis has an impact on salvage rates or patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In September 2011, Pediatric Radiology published a supplement containing the contents of a recent ALARA conference [1][2][3][4][5][6][7][8][9][10]. One month later, Radiology published an editorial titled "CT radiation dose: trending in the right direction" [11].…”
mentioning
confidence: 99%
“…Better methods for estimating actual patient dose are being suggested, as the limitations of indices such as CTDI and DLP are being taught [1,3,5,6]. Population dose is being decreased with reduction of inappropriate studies and formulation of appropriateness criteria [1,4,7,9,10]. Further dose reductions occur from optimizing CT techniques [1,4,7,8].…”
mentioning
confidence: 99%